Un nouvel habitat du Bronze final IIIb dans le Val d’Orléans et ses traces de métallurgie du fer : Bonnée, Les Terres à l’Est du Bourg (Centre, Loiret) - Stéphane Joly; Florent Mercey; Anne Filippini; Valérie Abenzoar; Morgane Liard; Frédéric Poupon (Revue Archéologique du Centre de la France)
The recent increase in the archaeological evaluations around the village of Bonnée has enabled the discovery of a final Bronze Age IIIb settlement (circa 900-750 BP) on about a hectare of the Terres à l’Est du Bourg. The limits inherent in this type of work restrict the interpretation of structures and all spatial approaches to this likely dwelling. The joint study of the different furnishings, in particular ceramics and metal, but also the cob and fauna, attests to its material culture and its interest. The slag could be amongst the oldest iron metallurgy remains from the Centre region. Some activities of post-forging are proven and certain operations are guessed at. The discovery of this settlement in this sector of the major bed of the Loire, has produced new data concerning the occupation of the land and its evolutionary problems in the valley of Orleans over these periods of transition in the early Hallstatt.